The relationship between gold price and exchange rate of Asean currencies (Ringgit Malaysia , Singapore Dollar, Thai Baht) against U.S. Dollar - Chin, Amy Ee Ling (Universiti Malaysia Sarawak (UNIMAS), 2011)
The empirical study is to examine relationship between gold price and exchange rate of ASEAN currencies such as Malaysian Ringgit (MYR/USD), Singapore Dollar (SGD/USD), and Thai Baht (THB/USD) against U.S. dollar. After the end of the Bretton Woods System and Gold Standard, the floating exchange rate has been adopted by most of the countries. Many have argued that the adoption of the floating exchange rate has been a major cause for the instability of world gold price. Currently, the gold price is dominated in U.S. dollar in which the change in dollar will influence the gold price in other currencies. The Augmented Dickey-Fuller (ADF) Unit Root Test, Johansen Cointegration Test, Granger Causality Test with Vector Error Correction Model (VECM) and Ordinary Least Square (OLS) Method are applied to examine the relationship between gold price and exchange rate of MYR/USD, SGD/USD and THB/USD on a monthly basis from January 1981 to December 2010. The result shows that long-term relationship exists between gold price and exchange rate of MYR/USD, SGD/USD and THB/USD. Nevertheless, there is no short-term relationship among them. Moreover, the result also indicates that gold price has positive relationship with MYR/USD but has inverse relationship with SGD/USD and THB/USD.